Use of Younger Patient Age and Greater Anterior Center-Edge Angle to Predict the Need for Bilateral Hip Arthroscopy in Patients With Bilateral Femoroacetabular Impingement–Related Hip Pain. Issue 8 (July 2021) - Knapik, Derrick M.; Clapp, Ian M.; Wichman, Daniel; Nho, Shane J.
Background: In patients with symptomatic femoroacetabular impingement syndrome, bilateral hip pain has been reported to occur in high frequency. However, not all patients require bilateral hip arthroscopy. Purpose: To determine the incidence, patient-specific variables, and postoperative outcomes in patients who presented with bilateral hip pain at the time of index hip arthroscopy and underwent subsequent contralateral arthroscopic hip surgery. Study Design: Case series; Level of evidence, 4. Methods: Patients who presented with bilateral hip pain, underwent primary hip arthroscopy between January 2012 and June 2018 for indication of femoroacetabular impingement syndrome, and had minimum 2-year follow-up were retrospectively analyzed. Baseline descriptive data, preoperative hip range of motion, and radiographic measurements were recorded with pre- and postoperative patient-reported outcomes (PROs). Independent samples t test was used to compare continuous variables, and chi-square test was used to compare categorical variables between patients undergoing unilateral and bilateral surgery. Bivariate correlations and a multivariable binary logistic regression were performed to determine factors predictive of the need for future contralateral hip arthroscopy. Results: In total, 108 patients were identified who reported bilateral hip pain during the index evaluation, underwent primary hip arthroscopy, and had 2-year follow-up. Among these, 42% (n = 45) elected to undergo hip arthroscopy on the contralateral hip at a mean of 6.0 months (range, 1-17 months) after the index surgery. Patients requiring bilateral surgery were significantly younger ( P = .004) and had a larger preoperative anterior center-edge angle (ACEA; P = .038) when compared with patients who had unilateral surgery. There were no significant differences in alpha angle measurements between patients who had unilateral and bilateral surgery. On bivariate analysis, younger age at the time of the index surgery ( r = −0.272; P = .005) and preoperative ACEA ( r = 0.249; P = .016) were significantly correlated with the need for bilateral surgery. On multivariate analysis, younger age remained a significant predictor for bilateral surgery (odds ratio, 0.95; 95% CI, 0.91-0.99). Patients who underwent bilateral hip arthroscopy reported significant improvement in all PROs ( P < .001), with a significantly greater mean Hip Outcome Score− Sports Specific Subscale score when compared with patients undergoing unilateral surgery ( P = .037). Conclusion: Subsequent contralateral hip arthroscopy was performed in 42% of patients who presented with bilateral hip pain. Younger age at the time of the index surgery and greater ACEA were predictive of the need for contralateral surgery. Patients undergoing bilateral surgery reported significantly improvement in PROs at minimum 2-year follow-up.